Empirical basis for adopting a theory-driven approach to preventing alcohol and other drug impairment (AOD) in the workplace. (1st March 2011) - Davey, T; Davey, J; Freeman, J; McClure, R
Abstract : Background: A State-based industry in Australia is in the process of developing a programme to prevent alcohol and other drug (AOD) impairment in the workplace. The objective of this study was to determine whether the Theory of Planned Behaviour can help explain the mechanisms by which behaviour change occurs with regard to AOD impairment in the workplace. Method: A survey of 1165 employees of a State-based industry in Australia was conducted, and a response rate of 98% was achieved. The survey included questions relevant to the Theory of Planned Behaviour: behaviour; behavioural intentions; attitude; perceptions of social pressure; and perceived behavioural control with regard to workplace AOD impairment. Findings: Less than 3% of participants reported coming to work impaired by AODs. Fewer than 2% of participants reported that they intended to come to work impaired by AODs. The majority of participants (over 80%) reported unfavourable attitudes toward AOD impairment at work. Logistic regression analyses suggest that, consistent with the theory of planned behaviour: attitudes, perceptions of social pressure and perceived behavioural control with regard to workplace AOD impairment, all predict behavioural intentions (p<0.001); and behavioural intentions predict (self-reported) behaviour regarding workplace AOD impairment (p<0.001). Conclusions: The Theory of Planned Behaviour appears to assist with understanding the mechanisms by which behaviour change occurs with regard to AOD impairment in the workplace. An occupational AOD programme which targets those mechanisms for change may improve its impact in preventing workplace AOD impairment.